Hubungan Pengetahuan, Mekanisme Koping Dan Dukungan Suami Dengan Kualitas Hidup Pada Wanita Menopause - Purnama Dewi, Bela; Stepane, Rosa (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2025)
Knowledge, Coping Mechanisms, and Husband Support are factors that can influence the quality of life of menopausal women. Menopause is often accompanied by physical and psychological changes that may reduce women's quality of life. Low levels of knowledge, the use of maladaptive coping mechanisms, and lack of husband support are factors that can worsen this condition. This study aimed to determine the relationship between knowledge, coping mechanisms, and husband support with the quality of life of menopausal women at Pustu Sungai Pasir in 2025. This research used a descriptive survey method with a purposive sampling technique, involving 65 respondents. Research instruments included the Menopause Knowledge Questionnaire, the Brief COPE Inventory to assess coping mechanisms, a husband support questionnaire, and the MENQOL (Menopause-Specific Quality of Life Questionnaire) to measure quality of life. Data were analyzed using the Chi-Square test. The results showed that the majority of respondents used adaptive coping mechanisms (55.4%), 47.7% reported low husband support, and 56.9% had a good quality of life. Statistical analysis indicated a significant relationship between knowledge, coping mechanisms, and husband support with the quality of life of menopausal women (p-value = 0.000). Based on these findings, it is recommended that menopausal women improve their knowledge, apply adaptive coping strategies, and utilize support from their husbands to enhance their quality of life